Liquid Modernity and Its Impact on the Poetry of Omar Ibn Abi Rabi'a (Journal of the College of Basic Education, 2025)
The study was formed into three sections preceded by a theoretical introduction to the phenomenon of modernity and followed by a brief conclusion about the most important results that the study came out with, in addition to establishing the most important sources and references. My approach in the first section was the breaking and artificiality of social ties, the second section was fear and uncertainty, and the third section was the breaking of the authority of social norms and the control of individualism.Introduction: Modernity has changed the components of human life, and redefined time, to give us new meanings more closely associated with capitalism in its advanced stages, and thus raised a question about the nature of humanity and its characteristics. Geography, its borders, meanings and content, and even all the peaks and incubators of human relations, balances of power and civilizational blocs have been redrawn. All relations of production, resources and relations have become intertwined, reflected on people and time. These two components are no longer the subject of science, but sciences have become reshaped in their methods and fields through the qualitative transformations witnessed by science. The mission of modernity was to release human freedom of choice from the captivity of the unseen, distrust and the absence of certainty in the ability of man to control the world, and to wage an unholy war to subject nature to science, and thus advance the wheel of freedom, guarantee individuality and bring man out of the iron cage of traditions. But traditions have not ended, but our understanding of them has changed, and history has not ended, but problems have occurred that require mixing the old with the modern, so the old is not the conversation did not continue and settle, but we found ourselves in a confused era, and that is fluidity.As for postponing things, it became the culture of the present, so postponing is a cultural practice that gained its independence in the new era of modernity, and derived its meaning and moral significance from the new significance of time, the time that travels towards a different present (and usually desirable) and preferred to the present that is lived now, and then living life as a journey is in essence a bottomless pit, it forces every present to serve something that has not yet been, and to serve it by shortening the distance, but by shortening the distance, everything meaningful and valuable will dissipate.The principle of postponing has become the rule of the age, like postponing satisfaction (postponing a need or desire, postponing a moment that represents a delicious experience, postponing pleasure and enjoyment), until postponing came to embody the modern scene, with phrases such as (not yet, not now) where effort was directed towards an unexpected result, which is what is known as the modern society.The aim of the study is to attempt to stand on the texts of liquid modernity in the poetry of Omar bin Abi Rabi'a, and to highlight the aesthetic and ideological aspects left by liquid modernity in his poetry. The study also seeks to direct this phenomenon from what is shared with it or adjacent to it from other social norms that were prevalent in the Umayyad era.